State-owned firms behind China's corporate debt - Molnar, Margit (OECD Publishing, 2019)
While China's overall debt-to-GDP ratio is not particularly high, its non-financial corporate debt relative to GDP is higher than in other major economies. State-owned enterprises account for over three quarters of that debt with a size exceeding GDP. This paper provides insights into the size of debt, leverage and debt service burden by various non-financial SOE groupings including by size, extent of state ownership, level of the owner, broad and detailed sector and region. Although the debt stock of local SOEs increased the fastest, firms under government agencies leveraged up more quickly and their debt service burden also grew most rapidly. SOEs in services industries increased their debt fastest, in particular in social services, transportation, real estate and construction. In turn, warehousing and real estate firms have the highest leverage. Firms in the three provinces of Xinjiang, Shanxi and Qinghai rank among the top five in all the three indicators of debt to revenues, leverage and debt service burden. Large SOEs owe most debt and leveraged up, while small and medium-size ones reduced their leverage. The surge in the debt service burden of small SOEs coincided with an increase in state assets in this group of firms. Sector-wise, state assets increased most in competitive industries. Empirical analysis shows that higher leverage and labour productivity are more conducive to a surge in SOE debt. Such surges appear to be triggered by falling interest costs, pointing to the role for easy monetary conditions in the rapid SOE debt accumulation. Recent corporate governance reforms of SOEs will likely act as disciplining device on SOE borrowing
Keywords: Economics; China, People's Republic